BOOKING TICKETS ONLINE AT PT CBB USING THE LARAVEL FRAMEWORK - R Kania; Edy Rakhmat; Yarham Fitrohiman Pahlawi (Teknik Informatika Fakultas Ilmu Komputer, 2022)
This web-based travel tour ticket booking application is a software application designed in general to process data related to travel ticket booking at PT Cahaya Berkah Bersama. The problem faced at PT Cahaya Berkah Bersama today is that travel ticket booking is not effective because customers have to contact or come directly to the office to book travel packages and know the details of travel packages that they want, calls from customers are often attached because the service admin is only one person, admins are often late to send travel tickets to customers. The method used in data collection in this research is the method of observation and interview. The program was developed using the PHP Programming Language of the Laravel Framework and the MySQL database. The design is built using HTML CSS and BOOTSTRAP 4. The expected result of the creation of this application is the creation of a travel ticket booking application that can make online bookings, does not take much time, is easily accessible to customers, and makes it easier for owners to view reports of booking transactions.